Treatment of depression in the elderly with repetitive transcranial magnetic stimulation using theta-burst stimulation: Study protocol for a randomized, double-blind, controlled trial - Valiengo, Leandro; Pinto, Bianca S.; Marinho, Kalian A. P.; Santos, Leonardo A.; Tort, Luara C.; Benatti, Rafael G.; Teixeira, Bruna B.; Miranda, Cristiane S.; Cardeal, Henriette B.; Suen, Paulo J. C.; Loureiro, Julia C.; Vaughan, Renata A. R.; et al. (Frontiers in Human Neuroscience, 2022)
Introduction Transcranial magnetic stimulation (TMS) is a consolidated procedure for the treatment of depression, with several meta-analyses demonstrating its efficacy. Theta-burst stimulation (TBS) is a modification of TMS with similar efficacy and shorter session duration. The geriatric population has many comorbidities and a high prevalence of depression, but few clinical trials are conducted specifically for this age group. TBS could be an option in this population, offering the advantages of few side effects and no pharmacological interactions. Therefore, our aim is to investigate the efficacy of TBS in geriatric depression. Clinical trial registration [https://clinicaltrials.gov/ct2/], identifier [NCT04842929].